Representation of illness in Familial Amyloidotic Polyneuropathy Portuguese Association newspaper: A documental study - Novais, Sónia (2018)
This study explores illness representations within Familial Amyloidotic Polyneuropathy Portuguese Association newspaper. A content analysis was performed of the issue data using provisional coding related to the conceptual framework of the study. All dimensions of illness representation in Leventhal’s Common Sense Model of illness cognitions and behaviors are present in the data and reflect the experience of living with this disease. Understanding how a person living with an hereditary, rare, neurodegenerative illness is important for developing community nursing interventions. In conclusion, we suggest an integration of common sense knowledge with other approaches for designing an intervention program centered on people living with an hereditary neurodegenerative illness, such as familial amyloidotic polyneuropathy.